Autobiography and social climbing - Peter Alheit (European Journal for Research on the Education and Learning of Adults)
The following essay touches on a highly interesting problem for politically sensitive adult education: What are the ‘costs’ of educational advancement? The answer is sought in biographies of three prominent examples: Pierre Bourdieu, Annie Ernaux and Didier Eribon. The data is based on autobiographically oriented reflections of the protagonists – symptomatically not ‘classic’ autobiographies. The concentration on France has to do with the fact that in the French cultural tradition this level of reflection – not least through the works of the selected authors – has gained a particular meaning. The selection itself relates to astonishing differences in the influences of historical times and the relevance of cohort experiences. The result of the analysis is undoubtedly an ‘essayistic dramatisation’, not a hasty generalisation, but it could stimulate scientific discussion and systematic empirical research.